Impact of magnetic field theory on blood flow and viscosity in a cylindrical tube - Pandey, Arun Kumar (Discover Molecules, 2025)
In this paper, we analyze a two-layered magnetohydrodynamic (MHD) flow within a cylindrical tube subjected to a transverse magnetic field. We derive analytical expressions for the velocity profiles in both the core and peripheral plasma layer (PPL) regions. Additionally, we investigate how the magnetic field affects blood flow rate and viscosity in the cylindrical tube, examining variations in the PPL thickness for different Hartmann numbers. The findings, presented through graphical analysis, highlight potential applications in minimizing cell damage and reducing dialysis durations for various medical conditions. Mathematics Subject Classification: 76D03, 76A05.